Dissolution and redistribution of trace elements and nutrients during dredging of iron monosulfide enriched sediments. (June 2018) - Choppala, Girish; Moon, Ellen; Bush, Richard; Bolan, Nanthi; Carroll, Neil
Abstract: The increased use of estuarine waters for commercial and recreational activities is one consequence of urbanisation. Western Australia's Peel-Harvey Estuary highlights the impacts of urbanisation, with a rapidly developing boating industry and periodic dredging activity. The aim of this research is to evaluate the potential mobility of nutrients and trace elements during dredging, and the influence of flocculation on iron and sulfur partitioning in iron monosulfide enriched sediments. Our findings indicate a short-term increase in nitrate, phosphate and ammonium, during dredging through the resuspension of sediments. However, no increase in metal mobilisation during dredging was observed except copper (Cu) and zinc (Zn). Flocculant addition increased the release of nutrients, zinc (Zn) and arsenic (As) from sediments, had no effect on acid volatile sulfides and pyritic sulfur, but corresponded with an initial sharp rise in elemental sulfur concentrations. The run-off water from geofabric bags should be treated to decrease the concentrations of Zn and As to their background levels before releases into the estuary. Long-term impact of dredging on organic matter mineralisation and its subsequent effect on nutrients and trace elements dynamics needs further investigation. Highlights: Trace elements and nutrients during dredging of sediments were monitored. Nitrate, nitrite, phosphate and ammonium were released during dredging. Trace elements in water, near dredging operations remained low except Cu and Zn. Flocculant addition to sediments increased elemental sulfur concentrations.